2020
DOI: 10.3390/en13205301
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Physics-Based Modeling and Neural Network Approach to Predict Cooling in Vehicle Integrated Thermal Management System

Abstract: Vehicle integrated thermal management system (VTMS) is an important technology used for improving the energy efficiency of vehicles. Physics-based modeling is widely used to predict the energy flow in such systems. However, physics-based modeling requires several experimental approaches to get the required parameters. The experimental approach to obtain these parameters is expensive and requires great effort to configure a separate experimental device and conduct the experiment. Therefore, in this study, a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the automobile industry, efforts are being undertaken to use machine learning in areas that incur substantial time and cost. For example, machine learning has been applied to safety and failure detection [13,14], driver classification [15], vibration [16], calibration [17], and system modeling [18], etc. In addition, the need for explainable artificial intelligence has emerged recently, and the predictive model contributions of machine learning features through SHAP (SHapley Additive exPlanations) value [19] are being used [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the automobile industry, efforts are being undertaken to use machine learning in areas that incur substantial time and cost. For example, machine learning has been applied to safety and failure detection [13,14], driver classification [15], vibration [16], calibration [17], and system modeling [18], etc. In addition, the need for explainable artificial intelligence has emerged recently, and the predictive model contributions of machine learning features through SHAP (SHapley Additive exPlanations) value [19] are being used [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that comparing with the vapor injection heat pump without WHR, the heating capacity and COP of the heat pump at 2 kW waste heat were increased by 1.61% and 1.38%, respectively. Chio et al [17] proposed a vehicle integrated thermal management system (VTMS) for improving the energy efficiency of vehicles. The proposed neural network model proved to be effective in predicting the characteristics of a vehicle cooling system.…”
Section: Introductionmentioning
confidence: 99%